Karakteristik Sedimen Permukaan Dasar Laut Berdasarkan Data Seismik Di Perairan Bengkalis Utara - Kirana, Widiah Dwi; Manik, Henry Munandar; Setyanto, Agus (Universitas Diponegoro, 2025)
The northern waters of Bengkalis Island, Riau Archipelago, represent a coastal region vulnerable to abrasion and anthropogenic pressures such as sand mining and marine traffic. This study employs an integrative approach combining seismic reflection methods and grain-size analysis from grab-sampler data to quantitatively assess the characteristics of surface seafloor sediments. Seismic sections from three profiles reveal a relatively flat seabed topography, with depths ranging from 9.5 to 14.9 meters and total sediment layer thickness reaching up to 76.5 meters. Data processing through AGC, FFT, bandpass filtering, and sparse spike deconvolution produced sharp and informative seismic sections, with estimated reflection coefficient values ranging from 0,245 to 0,257. The interpretation results indicate consistency between the reflection coefficients extracted from seismic data and the theoretical values derived from sediment grain sizes of 0,021–0,025 mm, classified as coarse silt. These findings reinforce the effectiveness of hydroacoustic methods in sediment characterization within coastal environments. This approach is considered efficient, broadly spatially covered, and holds strategic potential for shallow marine sedimentology studies. Perairan Bengkalis Utara, Kepulauan Riau, merupakan wilayah pesisir yang rentan terhadap abrasi dan tekanan antropogenik seperti penambangan pasir dan pelayaran. Penelitian ini menggunakan pendekatan integratif antara metode seismik refleksi dan analisis ukuran butir sedimen dari penginti comot (grab sampler) untuk mengkaji karakteristik sedimen permukaan dasar laut secara kuantitatif. Penampang seismik dari tiga lintasan menunjukkan topografi dasar laut yang relatif datar, dengan kedalaman seabed antara 9,5 hingga 14,9 meter dan ketebalan total lapisan sedimen mencapai 76,5 meter. Pengolahan data melalui tahapan AGC, FFT, bandpass filter, dan dekonvolusi menghasilkan visualisasi penampang yang tajam dan informatif, serta estimasi koefisien refleksi dalam kisaran 0,245–0,257. Hasil interpretasi menunjukkan kesesuaian nilai koefisien refleksi dari data seismik dengan nilai teoritis berdasarkan ukuran butir sedimen sebesar 0,021–0,025 mm, yang diklasifikasikan sebagai lanau kasar. Temuan ini memperkuat efektivitas metode hidroakustik dalam karakterisasi sedimen di wilayah pesisir. Pendekatan ini dinilai efisien, luas cakupannya, dan potensial menjadi metode strategis dalam studi sedimentologi laut dangkal.